Chinese Urban Young Women's Preferences And Perceptions Toward International Cosmetic Magazine Advertising - Lu, Xi (2006)
Advertising is regarded as the most effective tool for multinationals to communicate with their target consumers. Further, understanding target consumers' perceptions and preferences can help advertisers implement advertising strategy more easily and effectively. However, as the implementation of China reform and openness policy in 1979, the society has a tendency toward modernisation and Westernisation, and Chinese urban young women become more opened, experienced, and affluent for shopping foreign goods and brands. This may generate some distinctive features and characteristics for their perceptions and attitudes toward advertising.